2019
DOI: 10.1002/jbio.201900043
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of Photobiomodulation Therapy: An in vitro and in vivo study

Abstract: Laser therapy, also known as Photobiomodulation (PBM) is indicated to reduce pain associated with different pathologies and applied using protocols that vary in wavelength, irradiance and fluence. Its mechanisms of action are still unclear and possibly able to directly impact on pain transmission, reducing nociceptor response. In our study, we examined the effect of two specific laser wavelengths, 800 and 970 nm, extensively applied in the clinical context and known to exert important analgesic effects. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 49 publications
3
16
3
1
Order By: Relevance
“…To note, these results confirmed only partially the findings of our previous study [ 13 ] where a reduction of calcium peak was achieved only with the 970 nm wavelength and 6 J protocol, meanwhile in the current work both the wavelengths delivered singularly and the combination of the two were effective. A possible explanation of the difference encountered could be ascribed to the cells employed, primary DRG neurons in our previous work [ 13 ] and an immortalized DRG cell line in the present study. Indeed, primary neurons are not able to divide, meanwhile the 50B11 cells are able to multiply indefinitely, so some phenotypic differences can be expected, [ 24 ] also in the response to a stimulus, as the laser light.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To note, these results confirmed only partially the findings of our previous study [ 13 ] where a reduction of calcium peak was achieved only with the 970 nm wavelength and 6 J protocol, meanwhile in the current work both the wavelengths delivered singularly and the combination of the two were effective. A possible explanation of the difference encountered could be ascribed to the cells employed, primary DRG neurons in our previous work [ 13 ] and an immortalized DRG cell line in the present study. Indeed, primary neurons are not able to divide, meanwhile the 50B11 cells are able to multiply indefinitely, so some phenotypic differences can be expected, [ 24 ] also in the response to a stimulus, as the laser light.…”
Section: Discussionsupporting
confidence: 92%
“…[ 16 ] In the pre‐irradiated cells, we observed a decrement of the calcium peak after capsaicin dispensation with almost all PBMT protocols, being the most efficacious the PBMT setting number 12, that is, the combination of 800 and 970‐nm wavelengths and energy of 18 J. To note, these results confirmed only partially the findings of our previous study [ 13 ] where a reduction of calcium peak was achieved only with the 970 nm wavelength and 6 J protocol, meanwhile in the current work both the wavelengths delivered singularly and the combination of the two were effective. A possible explanation of the difference encountered could be ascribed to the cells employed, primary DRG neurons in our previous work [ 13 ] and an immortalized DRG cell line in the present study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A study reported that 660 nm laser increased ROS production, the 800 nm laser reduced ROS production while 970 nm laser produced a moderate anti-oxidant activity in neutrophil polymorphonuclear granulocytes and keratinocytes (29). Zupin et al (30) demonstrated that LLLT effect differs between 800 and 970 nm with 800 nm increased mitochondrial membrane potential and ROS production while 970 nm reduced calcium flow among dorsal root ganglion neurons. In contrast to energy density, the wavelength could influence mitochondrial changes in a less predictable manner.…”
Section: Metabolismmentioning
confidence: 99%
“…However, it is important to note the big difference in mitochondrial responses resulting from a small difference in wavelengths of <200 nm (29,30). Some wavelengths (660, 800, and 970 nm) would have similarly boosted cell proliferation, however the mitochondrial responses were diametrically different.…”
Section: Metabolismmentioning
confidence: 99%